2013
DOI: 10.3390/molecules18066383
|View full text |Cite
|
Sign up to set email alerts
|

[Fe2L3]4+ Cylinders Derived from Bis(bidentate) 2-Pyridyl-1,2,3-triazole “Click” Ligands: Synthesis, Structures and Exploration of Biological Activity

Abstract: A series of metallosupramolecular [Fe 2 L 3 ](BF 4 ) 4 "click" cylinders have been synthesized in excellent yields (90%-95%) from [Fe(H 2 O) 6 ](BF 4 ) 2 and bis(bidentate) pyridyl-1,2,3-triazole ligands. All complexes were characterized by elemental analysis, IR, UV-vis, 1 H-, 13 C-and DOSY-NMR spectroscopies and, in four cases, the structures confirmed by X-ray crystallography. Molecular modeling indicated that some of these "click" complexes were of similar size and shape to related biologically active pyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 102 publications
4
53
0
Order By: Relevance
“…Additionally, the spectrum of 2a is very similar to the previously reported iron(II) analogue (Fig. 1c) [51,57]. Further support for the formation of the ruthenium(II) helicate was obtained from 1 H DOSY NMR spectroscopy (Supporting information).…”
Section: Synthesismentioning
confidence: 52%
See 1 more Smart Citation
“…Additionally, the spectrum of 2a is very similar to the previously reported iron(II) analogue (Fig. 1c) [51,57]. Further support for the formation of the ruthenium(II) helicate was obtained from 1 H DOSY NMR spectroscopy (Supporting information).…”
Section: Synthesismentioning
confidence: 52%
“…We [39][40][41][42][43][44] and others [45][46][47][48][49][50][51][52][53][54][55] have explored the use of 1,4-disubstituted 1,2,3-triazole containing ''click'' ligands in the development of functionalized metallosupramolecular architectures and have shown that metallomacrocycles, cages and helicates can be readily generated. As part of that work we developed a small family of bis-2-(1-R-1H-1,2,3-triazol-4-yl)pyridine ligands 1 [56] (Scheme 1) and showed that they would assemble into [Fe 2 L 3 ] 4+ metallosupramolecular helicates [57] when treated with Fe(II) ions. Molecular modeling indicated that some of these ''click'' complexes were of similar size and shape to the biologically active pyridylimine-based iron(II) helicates and suggested that the ''click'' complexes may bind to both duplex and triplex DNA.…”
Section: Introductionmentioning
confidence: 99%
“…In order to gain some structural information on the cobalt(III) cylinders derived from L1 and L2, we synthesised the related iron(II) complex Unfortunately, despite extensive efforts, crystals of the cobalt(III) cylinders of the quality required for X-ray diffraction (XRD) studies could not be obtained [51]. The analogous [Fe 2 L3 3 ](BF 4 ) 4 , and [Ru 2 L3 3 ](PF 6 ) 4 cylinders have been previously crystallographically characterised and were found, in both cases, to be racemic mixtures of the ∆∆ and ΛΛ helicates [30,32,33]. In order to gain some structural information on the cobalt(III) cylinders derived from L1 and L2, we synthesised the related iron(II) complex [ (Figure 1b and Supplementary Materials, Figure S30).…”
Section: Cylinder Design and Synthesismentioning
confidence: 99%
“…These "click" ligands have been exploited for a range of purposes including the construction of metallosupramolecular macrocycles [26][27][28][29] and helicates [30,31]. In a previous work, we have exploited "click" ligands to synthesise triply [32,33] and quadruply [34] stranded helicates and explored the biological activity of these systems. We showed that a dipalladium quadruply stranded helicate had good cytotoxicity (IC 50 = 3-7 µM) against three different cancer cell lines; however, disappointingly, the complex displayed no selectivity towards non-cancerous phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation